The relationship of state of total ozone over antarctic station Vernadsky with state of ozone hole over Antarctic - V. F. Martazinova; E. K. Ivanova (Ukrainian Antarctic Journal, 2015)
The change of total ozone over the station Vernadsky / Faraday is investigated since 1996 for the period after the transfer of the British Antarctic Survey (BAS) station to the Ukraine. During this period there is a marked depletion of the ozone layer over Antarctica. Comparison of average annual variation of total ozone on measurements at the station Vernadsky / Faraday of 1972 to 1994 and 1995 to 2012 showed that the ozone hole in the period 1972-1994 was not appeared. We propose here a new approach to the classification of curves of the annual variation of total ozone over Ukraine Antarctic station (UAS) in the last decades.